Simplified Silvestrol Analogues with Potent Cytotoxic Activity. Issue 7 (27th March 2014) - Hawkins, Bill C.; Lindqvist, Lisa M.; Nhu, Duong; Sharp, Phillip P.; Segal, David; Powell, Andrew K.; Campbell, Michael; Ryan, Eileen; Chambers, Jennifer M.; White, Jonathan M.; Rizzacasa, Mark A.; Lessene, Guillaume; et al.
Abstract The complex natural products silvestrol (1) and episilvestrol (2) are inhibitors of translation initiation through binding to the DEAD‐box helicase eukaryotic initiation factor 4A (eIF4A). Both compounds are potently cytotoxic to cancer cells in vitro, and 1 has demonstrated efficacy in vivo in several xenograft cancer models. Here we show that 2 has limited plasma membrane permeability and is metabolized in liver microsomes in a manner consistent with that reported for 1. In addition, we have prepared a series of analogues of these compounds where the complex pseudo‐sugar at C6 has been replaced with chemically simpler moieties to improve drug‐likeness. Selected compounds from this work possess excellent activity in biochemical and cellular translation assays with potent activity against leukemia cell lines.